r 2014
DOI: 10.20955/r.96.331-357
|View full text |Cite
|
Sign up to set email alerts
|

Student Loan Debt: Can Parental College Savings Help?

Abstract: ollege costs are high and continue to grow as American students and their families are borrowing at unprecedented rates to keep pace with the increasing costs. The College Board (2012a), which produces an annual report tracking college costs, estimates the total annual cost of college attendance plus room and board at a private four-year college rose by 4.2 percent in 2012-13 to $29,056 (College Board, 2012a). Even the traditionally more affordable in-state, public four-year college costs were $8,655 for the 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 40 publications
1
13
0
Order By: Relevance
“…Walsemann, Gee, and Gentile (2015) found that student loans were significantly associated with poorer psychological functioning among college students. Outstanding student debt was also associated with weaker financial health and lower net worth (Elliott & Nam, 2013; Fry, 2014), lower retirement savings (Elliott, Grinstein-Weiss, & Nam, 2013), and lower likelihood of purchasing a home (Gicheva & Thompson, 2015).…”
Section: Student Debt and Trajectories Of Sfwbmentioning
confidence: 99%
“…Walsemann, Gee, and Gentile (2015) found that student loans were significantly associated with poorer psychological functioning among college students. Outstanding student debt was also associated with weaker financial health and lower net worth (Elliott & Nam, 2013; Fry, 2014), lower retirement savings (Elliott, Grinstein-Weiss, & Nam, 2013), and lower likelihood of purchasing a home (Gicheva & Thompson, 2015).…”
Section: Student Debt and Trajectories Of Sfwbmentioning
confidence: 99%
“…Some studies suggest that the value of assets may be a better gauge of overall financial health than net worth, because these focus on the results of human capital development, rather than counting student debt as a liability, as in net worth measures. Elliott, Grinstein‐Weiss, and Nam () use the 2007–2009 SCF panel to assess whether student loan debt is associated with total assets. Their findings indicate that median 2009 assets for households with no outstanding student loan debt were higher than those for households with outstanding student loan debt ($207,000 in 2009 vs. $174,000 in 2007).…”
Section: Literature Reviewmentioning
confidence: 99%
“…We follow the theoretical framework as specified in Elliott, Grinstein‐Weiss, and Nam () to address our first question.…”
mentioning
confidence: 99%
“…A few studies have argued the important role of college savings (Elliott & Nam, ; Elliott, Song, & Nam, ). When parents open college savings accounts, students were more likely to report paying for their college attendance with family contributions (Elliott & Nam, ). Even small amounts in a child's savings accounts influenced both college enrollment and graduation (Elliott et al., ).…”
Section: Theories Related To Student Loan Debtmentioning
confidence: 99%